Linking sensory processing challenges to autism-related factors: observational evidence from Pakistan - Sana Khawer; Mohammad Ismail; Sitwat Zehra (Middle East Current Psychiatry)
Abstract Background Sensory processing dysfunction (SPD) is a salient feature of autism spectrum disorder (ASD) that has garnered substantial clinical and research attention. Individuals with ASD often exhibit atypical responses to sensory stimuli, including hypersensitivity, hyposensitivity, and seeking behaviors across multiple modalities. These sensory challenges frequently contribute to the disorder’s core symptoms, influencing social interactions, communication abilities, and repetitive behaviors. However, the precise relationship of SPD with ASD characteristics is not well understood. This study aimed to identify the association between SPD behaviors and regression of milestones, severity of ASD, and age of children with ASD. This observational study was conducted on 112 ASD patients (3–16 years, 6.88 SD ± 3.18). The inclusion criteria for ASD patient recruitment required an ASD diagnosis by a healthcare professional, based on the criteria outlined in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). After signing an informed written consent form, the parents and therapists filled out Winnie Dunn’s Short Sensory Profile (SSP) questionnaire. The data collection included sensitivities on tactile, oral/olfactory, vestibular, proprioception, visual/auditory inputs, and energy profiles of children with ASD, gauged as a typical performance, probable difference, and definite difference using a Likert scale. Results This study highlights the significant association between SPD and ASD factors, such as milestones regression (MR), severity of ASD, and age of patients. Key findings include significant associations between MR and vestibular dysfunction, visual/auditory, and auditory filtering. The study also indicated a significant association between the severity of ASD (CARS scores) and tactile dysregulation (p < 0.001). Furthermore, the age of the patients was significantly correlated with vestibular, visual/auditory processing, auditory filtering, and energy profiles of the ASD patients (p < 0.001). Conclusions These findings can be utilized to understand the pattern of sensory challenges associated with ASD factors. They may assist practitioners in developing targeted interventions, potentially reducing costs and intervention time while improving outcomes for individuals with ASD.